MODEL PROBLEM BASED LEARNING (PBL) PADA PEMBELAJARAN BERDIFERENSIASI BERBANTUAN MEDIA QUIZIZZ TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS V DI SEKOLAH DASAR - Safitri, Ani; Nuhyal Ulia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research fon examining the effectiveness of the Problem Based Learning (PBL) model in differentiated learning assisted by Quizizz media on the mathematical communication skills of fifth students at SD Negeri Menur. This study employs a Quasi-Experimental design using a Nonequivalent Control Group Design. The population and sample in this study consist of class VA (control) and class VB(Eksperiment) each with 18 students, totaling 36 students, selected using the simple random sampling method. Data collection techniques used in this research include observation, interviews, and documentation studies. The data analysis techniques applied are normality test, homogeneity test, independent t-test, paired t-test, and N-gain test. The research results from the independent t-test and paired t-test showed a sig. (2-tailed) of 0.000 < 0.05, leading to the rejection of Ho and acceptance of Ha. This indicates that the Problem Based Learning (PBL) model in differentiated learning by Quizizz media is effective in improving the mathematical communication skills of V students at SD Negeri Menur on the topic of addition and subtraction of fractions, with average pretest score of 54.4 and the average posttest score of 84.4 in the experimental class.